2005
DOI: 10.1111/j.1471-4159.2005.03194.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N‐acetylaspartylglutamate (NAAG) on non‐quantal and spontaneous quantal release of acetylcholine at the neuromuscular synapse of rat

Abstract: N-Acetylaspartylglutamate (NAAG), known to be present in rat motor neurons, may participate in neuronal modulation of nonquantal secretion of acetylcholine (ACh) from motor nerve terminals. Non-quantal release of ACh was estimated by the amplitude of the endplate membrane hyperpolarization (H-effect) caused by inhibition of nicotinic receptors by (+)-tubocurarine and acetylcholinesterase by armin (diethoxyp-nitrophenyl phosphate). Application of exogenous NAAG decreased the H-effect in a dose-dependent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 84 publications
(219 reference statements)
0
29
0
Order By: Relevance
“…Experiments on rat NMJ showed that NAAG is able to depress non-quantal ACh release [90]. The mechanism of neuropeptide action is realized through its extracellular hydrolysis by the GCP II with the formation of glutamate molecules, which, as was shown earlier [89], activate glutamate postsynaptic NMDA receptors and thereby trigger the NO-mediated mechanism of reducing the intensity of the non-quantal ACh release [104].…”
Section: Peptidergic Signalingmentioning
confidence: 90%
See 3 more Smart Citations
“…Experiments on rat NMJ showed that NAAG is able to depress non-quantal ACh release [90]. The mechanism of neuropeptide action is realized through its extracellular hydrolysis by the GCP II with the formation of glutamate molecules, which, as was shown earlier [89], activate glutamate postsynaptic NMDA receptors and thereby trigger the NO-mediated mechanism of reducing the intensity of the non-quantal ACh release [104].…”
Section: Peptidergic Signalingmentioning
confidence: 90%
“…In the later stages of amphibians development, namely in tadpoles and adult frogs metabotropic glutamate receptors were found [80,[84][85][86], which, apparently, are localized postsynaptically [80,85]. In contrast to the amphibian NMJ, in the endplate of mammals to date were found only ionotropic glutamate NMDA and AMPA receptors, and all the experimental data show exclusively postsynaptic localization of these proteins [87][88][89][90][91][92].…”
Section: Glutamatergic Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of Na + -, K + -, Cl --cotransport is one of the key stage in the development of denervationinduced alterations in MF, including the increase in MF volume [1,6]. It was previously found that the intensity of this co-transport is controlled by the inhibitory action of the motoneuron realized via activation of glutamate receptors located on the sarcolemma [2,6].Motor nerve terminals in rats contain dipeptide N-acetylaspartylglutamate (NAAG) [3] participating in the synaptic transmission as an agonist of ionotropic glutamate NMDA-and metabotropic mGlu3-receptors [7,8] or as a glutamate precursor produced during hydrolysis catalyzed by glutamate carboxypeptidase II [4,5].Our aim was to study the possible role of NAAG in the neurotrophic control of MF volume. …”
mentioning
confidence: 99%